First report of antiparasitic resistance to ivermectin in guinea pigs from Cajamarca, Peru - Rojas-Moncada, Juan (2023)
The aim of this study was to determine the efficacy of three frequently drugs used in the treatment of nematodes in guinea pigs at the Baños del Inca Experimental Station of the National Institute of Agricultural Innovation (INIA), Cajamarca. Forty male guinea pigs of the Inka line between 2 to 3 months of age, positive for Trichuris spp and Paraspidodera uncinata, naturally infected, and reared within the same management and feeding system were used. The guinea pigs were homogeneously distributed according to the number of eggs per gram of faeces in 20 positive for Paraspidodera uncinata and 20 for Trichuris spp, distributed in four groups of five each. The treatments were T0: control group, not dosed; T1: fenbendazole 20 mg/kg, PO; T2: oxfendazole 20 mg/kg, PO; and T3: ivermectin 0.5 mg/kg, SQ. The evaluation was carried out by necropsy on day 10 of dosing using the the Randomized Controlled Trial. An efficacy of 100% was determined for fenbendazole and oxfendazole against Trichuris spp and P. uncinata, while ivermectin was 91% effective against P. uncinata and 68% against Trichuris spp. It is concluded that, in INIA-Cajamarca guinea pigs, P. uncinata and Trichuris spp were susceptible to fenbendazole and oxfendazole, and resistant to ivermectin.